Animals - Elizabeth Leane (2019)
It is difficult to imagine a travel narrative that does not include some mention of encounters with nonhuman beings. There are very few places to which humans can travel that are not already inhabited and traversed by other species. The Antarctic plateau and outer space might qualify, but even then, animals trail-blazed - or, more accurately, were forced to trail-blaze - the routes. The first humans to reach the South Pole - a Norwegian team led by Roald Amundsen in 1911 - used sledges pulled by Greenland huskies, and one of the first human acts at the so-called 'last of all places' was the slaughter of a dog named Helge, who was 'portioned out on the spot' to provide food for his companions. Monkeys, mice, rats, rabbits and dogs reached space before humans, many of them dying as a result. In more mundane locations, animals have been and are ubiquitous, transporting, accompanying, assisting, intriguing, ignoring, pestering, threatening and occasionally eating human travellers, and themselves in turn being ridden, harnessed, transported, mistreated, befriended, photographed, pursued, classified, hunted, killed and frequently consumed. It is no surprise, then, that almost any travel narrative read with attentiveness to the presence of animals will yield incidents of some kind every few pages, some trivial, some highly revealing. More surprising is the relative paucity of criticism focusing on animals in travel writing - both individual animals and particular species. To the extent that travel writing studies is a branch of literary studies, this neglect reflects prevailing approaches (until recently) within this larger field. Literary critics have not entirely ignored animals in the texts they study, but rather have tended to consider them interesting only where they can be read as figures for human qualities. This tendency to look through rather than at the textual animal can also be found in analyses of animals in travel texts. While figurative uses of animals can of course be relevant to actual animals, ...